Maternal Iron, Copper, Magnesium and Calcium Levels in Preterm Delivery and the Effect of These Trace Elements on Birth Weight - Demirtürk, Fazlı; Aytan, Hakan; Çalışkan, Ahmet; Himmetoğlu, Özdemir; Güngör, Tayfun (Gynecology Obstetrics & Reproductive Medicine, 2006)
OBJECTIVE: To compare the maternal micronutrient levels in patients suffering from preterm delivery and women with term pregnancies and to assess the effect of maternal serum micronutrient levels on birth weight. STUDY DESIGN: Fifty preterm laboring pregnant women and 20 term pregnant women were enrolled. Serum iron, magnesium, copper and calcium levels were measured with “flamed atomic absorption technique”. Hemoglobin levels, gestational age, birth weight, Apgar scores of the first and fifth minutes, socioeconomic status and smoking habits were evaluated. RESULTS: The mean value of serum iron levels was statistically lower in preterm group when compared with the term group. Other micronutrient levels were not differing. Birth weight, Apgar scores of the first and fifth minutes, gestational ages, hemoglobin and serum iron levels were found to be significantly lower in preterm group (p<0.001). Maternal serum iron levels, and hemoglobin levels were found to be correlated with gestational age and birth weight; however, with regression analysis only iron was found to be an independent factor affecting gestational age and birth weight. CONCLUSION: Maternal serum iron level is linearly correlated with birth weight and infant birth weight, but other micronutrients seem to have no association with preterm delivery and birth weight.